UPAYA MENINGKATKAN KEMANDIRIAN DENGAN METODE BERMAIN PERAN PADA ANAK USIA 3-4 TAHUN DI KELOMPOK BERMAIN DARMA PUTRA KECAMATAN LUBUK DALAM KABUPATEN SIAK - ', Susanti; Novianti, Ria; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The background of this research based on the observation in â€˜DarmaPutraâ€ play group age 3 -4 years old consist of 12 children only 4 children shownindependent behavior and join learning activity. Without their parents. The children goto toiled without help, they put their bag in the right place, they eat by themselves, theycan put the toys in to rack toy, and they able choose play activity by themselves. Inreality, these are 8 children show the behavior as below : there are children play in thegroup with their parents. Children cannot cremation by themselves, children can notput their bag in to the right place. In this case described that the independent ofchildren still low. The aimed of this research : 1) to know the independency of childrenby using of the role play. 2) to know the implementation of role play In independencyimproment. 3) to know the independency level improvement for children age 3-4 yearsold by using role play method in darma putra playgroup. Its 12 children, consist 7women and 5 toys. This research held on april until june 2014. The data will beprocess byobservation. From the result and discussion, the research makesummarizing as below : the role play can improve the independency of the children age3-4 years old in darma putra playgroup about 89,27 % compare the early data orbefore method implementation with children independency in circlus II.Keywords : Effort, Indepedency role paly, Children.